1975
DOI: 10.1037/0022-3514.32.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Erotic stimuli and aggression: Facilitation or inhibition.

Abstract: The present experiment attempted to reconcile previous results on the relationship of erotic stimuli and aggression. Subjects were either insulted or not insulted prior or subsequent to observing erotic stimuli of varying levels of arousal inducements. It was found, in support of prior research, that mildly erotic stimuli had an inhibiting effect on aggression when viewed subsequent to anger arousal, whereas highly erotic stimuli tended to maintain aggression at a level similar to nonerotic exposure. Prior vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(48 citation statements)
references
References 17 publications
6
41
1
Order By: Relevance
“…Viewing pornography has been found to have many negative consequences for the individual, including impairment of academic and professional performance, distress, sexual compulsivity (Cooper, Putnam, Planchon, & Boies, 1999; Manning, 2006), and aggression (Allen, D’Alessio, & Brezgel, 1995; Donnerstein, Donnerstein, & Evans, 1975). Beyond the problems related to self, SEM use has increased difficulties in intimate relationships (Deloy, 2007; Oddone-Paolucci, Genuis, & Violato, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Viewing pornography has been found to have many negative consequences for the individual, including impairment of academic and professional performance, distress, sexual compulsivity (Cooper, Putnam, Planchon, & Boies, 1999; Manning, 2006), and aggression (Allen, D’Alessio, & Brezgel, 1995; Donnerstein, Donnerstein, & Evans, 1975). Beyond the problems related to self, SEM use has increased difficulties in intimate relationships (Deloy, 2007; Oddone-Paolucci, Genuis, & Violato, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The arousal-followed-by-provocation order has been used in two other studies involving other types of prior arousal. Zillmann and Bryant (1974), using physical exercise, and Donnerstein et al (1975), using erotica, have also found that arousal prior to provocation increases retaliatory aggressiveness in males. [400] It may be argued that the present procedural order provides a more useful analogue than the traditional order to the typical media-viewing situation.…”
mentioning
confidence: 97%
“…It is important to note that our theoretical analysis of triggered displaced aggression appears to share some conceptual similarities with Zillman's (1971Zillman's ( , 1979 excitation transfer theory. In Zillman's typical paradigm, a manipulation of the presence or absence of an initial provocation is followed by a subsequent manipulation of arousal such as noise (e.g., Donnerstein & Wilson, 1976;Konecni, 1975), an erotic film (e.g., Cantor, ZiJlman, & Einsiedel, 1978;Donnerstein, Donnerstein, & Evans, 1975;Zillman, 1971), or physical exercise (e.g., Zillman, Katcher, & Milavsky, 1972). In general, Zillman's results show that the nonprovoking subsequent arousal only increases aggression when it is preceded by an initial provocation, although there are exceptions in which arousal-induced increases in aggression are seen in the absence of prior provocation (e.g., Jaffe, Malamuth, Feingold, & Feshbach, 1974).…”
Section: Excitation Transfer and Displaced Aggressionmentioning
confidence: 99%